EVALUATION OF PRODUCTIVE BEHAVIOR OF Cyclanthera pedata IN A ACUAPONIC AND CONVENTIONAL CULTURE - YARINACOCHA - TANKAMASH UGKUCH, Elmo (2018)
The aim of this research was to evaluate the productive behavior of Cyclanthera pedata in an aquaponic and conventional crop in the District of Yarinacocha, Ucayali Region. The aquaponic system was supported by the breeding of Piaractus brachypomus "Paco", conditioned in aging tanks. The seedlings were stored until they were 16.33 cm high, they were transplanted both in the log bed (with an irrigation system from the fish culture tanks, with 15 minutes of irrigation and 45 minutes of rest), as in ridges on the ground, the corresponding agronomic management was performed, the Completely Random Design (DCA) was applied, with 2 treatments and 3 repetitions; It was determined that, the aquaponics cultivation of caigua, presented higher values ​​for number of immature fruits, fruit weight, number of fruits per hectare and yield per hectare; while the conventional system was better in terms of fruit length;  no significant differences were found for the fruit diameter in each production system.  The production of the caigua was affected by the percentage of survival, the percentages being low in both systems.